Rabindranath Tagore's The home and the world : a critical companion - Datta, Pradip Kumar (Delhi : Permanent Black ; New Delhi : Distributed by Orient Longman, 2002)
Contributed articles on Ghare baire, Bengali novel, and its English translation, The home and the world.
Includes bibliographical references.
Keywords: Tagore, Rabindranath, -- 1861-1941.